The complex polarization angles of radio pulsars: orthogonal jumps and interstellar scattering - Karastergiou, A (2009)
Despite some success in explaining the observed polarization angle swing of radio pulsars within the geometric rotating vector model, many deviations from the expected S-like swing are observed. In this Letter, we provide a simple and credible explanation of these variations based on a combination of the rotating vector model, intrinsic orthogonally polarized propagation modes within the pulsar magnetosphere and the effects of interstellar scattering. We use simulations to explore the range of phenomena that may arise from this combination, and briefly discuss the possibilities of determining the parameters of scattering in an effort to understand the intrinsic pulsar polarization. © 2008 The Author. Journal compilation © 2008 RAS.